The Problem that Wasn't : Coordination Failures in Sovereign Debt Restructurings - Zettelmeyer, Jeromin (IMF Working Papers; Working Paper ;, 2011)
Contrary to widespread expectation, debt renegotiations in the era of bond finance have generally been quick and involved little litigation. We present a model that rationalizes the initial fears and offers interpretations for why they did not materialize. When the exchange offer is sufficiently attractive vis-a-vis holding out, full participation can be an equilibrium. Legal innovations such as minimum participation thresholds and defensive exit consents helped coordinate creditors and avoid litigation. Unlike CACs, exit consents can be exploited to force high haircuts on creditors, but the ability of creditors to coordinate to block exit consents can limit overly aggressive use.